Pengaruh Gaya Kepemimpinan, Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Guru SMP Negeri 1 Mattiro Bulu Kabupaten Pinrang - H Hamdana (Doktor Ilmu Manajemen, Universitas Muslim Indonesia, 2020)
The data used are primary data and secondary data. In this study the population consists of all teachers SMPN 1 Mattiro Bulu Pinrang District as many as 56 teachers. Sampling as a whole because all members of the population used as a sample of the number of small population, so the number of samples equal to the total population of 56 respondents. Data collection is done through questionnaires, and documentation. Methods of data analysis using descriptive statistical analysis, and multiple linear regression using SPSS version 21 program.The results showed that: (1) leadership style, work environment and motivation have positive and significant effect on teacher performance at SMPN 1 Mattiro Bulu Pinrang Regency and (2) From the three independent variables that have significant influence in determining teacher performance level, it turns out that the motivation variable has a dominant influence in improving teacher performance in teacher SMPN 1 Mattiro Bulu Pinrang Regency.